Insulin pen use and diabetes treatment goals: A study from Iran STEPS 2016 survey. - Hedyeh Ebrahimi (PLoS ONE, 2019)
Background Frequency of insulin pen use, despite its higher costs, is increasing to substitute the traditional use of insulin vials. This study aims to report insulin pen use frequency and its associated factors among participants of the STEPS survey 2016 in Iran, which was conducted based on the World Health Organization (WHO) STEPS methodology. Methods In this cross-sectional study, 19,503 (mean age of 46.03±0.13) out of 30,541 participants of the Iran STEPS survey were included (Inclusion criteria: aged >25 years old and availability of their demographic, clinical, and laboratory results for serum glucose, HbA1c, and lipid profile). Clinical and demographic characteristics, a frequency of use of each diabetes mellitus treatment type, and the association of insulin pen use with health outcomes are reported using descriptive analysis and propensity score modeling. Results There were 1,999(10.85%) individuals diagnosed with diabetes in the population, while 1,160(56.87%) cases were taking antihyperglycemic treatments. In this subset, 240(21.14%) individuals administered insulin with or without using oral agents at the same time. 52.28% of participants who were under insulin therapy used insulin pens. None of the socioeconomic determinants, including gender (p-value = 0.11), type of residential areas (p-value = 0.52), years of schooling (p-value = 0.27), wealth index (p-value = 0.19), marital status (p-value = 0.37), and insurance types (p-value = 0.72) were significantly different among groups using insulin pens and insulin vials. Moreover, in the propensity score modeling, pen usage was not associated with a lower heart attack and ischemic stroke histories, systolic blood pressure, serum lipid profile, blood glucose, or HbA1c levels. Conclusion Results showed that the use of the higher-costing insulin pens compared to traditional vials and syringes is not associated with improved glycemic control and better lipid profile in our sample. Future studies are needed to confirm these findings and to compare other aspects of insulin pen use, including adherence to treatment and cost-effectiveness.